Selection of stevia elite genotypes aiming at the development of cultivars adapted to the Brazilian Savanna - Castro, Fellipe Celestino de; Faleiro, Fábio Gelape; Oliveira, Jamile da Silva; Amabile, Renato Fernando; Melo, João Victor Pinheiro (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2022)
In this work, the objective was to evaluate morphoagronomic traits, correlate and select elite genotypes of Stevia rebaudiana (Bert.) Hemsley with high productivity, and adapted to Brazilian Savanna conditions. A total of 230 genotypes were evaluated, from the Embrapa Cerrados Working Collection, from 2018 to 2019, with 24 evaluations, carried out in six cuts, with each cut representing a certain moment of generation of the response data of the analyzed genotypes. Four traits were analyzed: green biomass production (g), plant height (cm), tillering number and juvenile period of each individual. The means of the characteristics of each genotype were correlated according to Pearson's correlation coefficient. The Mulamba and Mock index was applied, with a selection intensity of 10%, to choose the superior genotypes. There are high positive correlations between juvenile period, height and green biomass production. The selected population were 23 superior genotypes, based on the application of rank sum resulting in high selection gains for the traits of interest. Finally, the selection of elite stevia genotypes with high production of green biomass, greater insensitivity to length of the daily light period, as well as taller plants, are essential for the continuity of the stevia breeding program on the Brazilian Savanna.